Clinical characteristics of patients with candida parapsilosis fungemia - Safiye Tasgin; Esma Eryilmaz-Eren; Hafize Sav; Aysegul Ulu Kilic (Journal of Global Antimicrobial Resistance)
INTRODUCTION: Candida parapsilosis is one of the main candida species isolated in hospital settings, and seriously affecting human health. The aim of this study is to reveal the clinical characteristics of patients hospitalized in our hospital with C. parapsilosis fungemia. METHODS: Adult patients with hospital-acquired C. parapsilosis fungemia in 2023 were included in the study. VITEk-2 system was used for Candida identification and antifungal susceptibility testing and patient data were accessed from the hospital data system. RESULTS: A total of 6402 blood cultures were studied from patients hospitalized and microorganisms were isolated in 1150 (18.0%) of them. 81 (7.0%) of the growths were Candida species, and 57 (70.4%) of the candida were C. parapsilosis.Most of the 46 patients who grew C. parapsilosis and were included in the study were patients hospitalized in intensive care units (39-84.8%). 28 (60.9%) of the patients were male and the median age was 73.5 (min 17-max 92).The underlying diseases and invasive procedures of the patients are summarized in Table 1. Central venous catheter (CVC) was inserted in 40 (87.0%) of the patients. The femoral region was preferred for 24 (52.2%) of the catheters. Antifungal susceptibilities are given in Table 3.Following C. parapsilosis growth, 28 (75.7%) of the patients died after a mean of 18.8 days. CONCLUSION: It was observed that the majority of patients with C. parapsilosis fungemia underwent invasive procedures. It is thought that these infections can be prevented by applying precautionary packages within the scope of infection control measures.